Economic globalization: who’s winning, who’s losing out? (Gütersloh, 2017)
"Two main consequences have arisen from the increasing cross-border exchange of goods, labor, capital and technologies: A better distribution of scarce production factors, resulting in positive growth effects for the economies of all countries involved. On the other hand, there have been changes in scarcity conditions within the individual economies. This leads to price changes in each country – both for material goods and services, as well as for the production factors of labor and capital. As a result, there are winners and losers of globalization within each country.